2020
DOI: 10.13171/mjc0200312162sh
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity of Some Organotin(IV) Chlorobenzoate Compounds against Plasmodium falciparum

Abstract: This paper reported the comparative study on antimalarial activity of some organotin(IV) derivatives with some chlorobenzoic acid derivatives used as the ligands. The compounds were synthesized by reacting the intermediate products of dibutyltin(IV) oxide, diphenyltin(IV) dihydroxide and triphenyltin(IV) hydroxide, with chlorobenzoic acid. The antimalarial activity was performed against Plasmodium falciparum. The results showed that the IC50 of the compounds tested were about the same with the chloroqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The results of in vitro antimalaria of 2 showed that this compound exhibits very high activity against Plasmodium, giving an IC50 value of 0.3 µg/mL (5.976 x 10 -7 M), and this is comparable with the control positive chloroquine with an IC50 value of 3 x 10 -7 M. This value is stronger than the antimalarial drug from the organotin (IV) compound, which has been reported lately [9,10,16] and may be better than other synthetic compounds having antimalarial activity which have been reported by others [17][18][19][20]. The data of activity test can be seen in Figure 8 and Table 2, while the data for the chloroquine are in Figure 9.…”
Section: In Vitro Antimalarial Of Artonin M (2)mentioning
confidence: 74%
See 1 more Smart Citation
“…The results of in vitro antimalaria of 2 showed that this compound exhibits very high activity against Plasmodium, giving an IC50 value of 0.3 µg/mL (5.976 x 10 -7 M), and this is comparable with the control positive chloroquine with an IC50 value of 3 x 10 -7 M. This value is stronger than the antimalarial drug from the organotin (IV) compound, which has been reported lately [9,10,16] and may be better than other synthetic compounds having antimalarial activity which have been reported by others [17][18][19][20]. The data of activity test can be seen in Figure 8 and Table 2, while the data for the chloroquine are in Figure 9.…”
Section: In Vitro Antimalarial Of Artonin M (2)mentioning
confidence: 74%
“…The in vitro antimalarial assay was performed following the procedures available in the literature and have been used previously in some of our publications [8][9][10]. However, the in vivo antimalarial test was carried out based on the procedure used published methods available in the literatures [11] and have also been used in our previous work [4].…”
Section: Antimalarial Activitymentioning
confidence: 99%
“…Antioxidant Activity Tests a) DPPH technique Antioxidant activity was measured using the 1,1-diphenyl-2-picrylhydrazine (DPPH) technique, as described by others [39][40][41]. The compounds were dissolved in methanol at different concentrations of 2; 4; 8; 16, and 32 M, respectively.…”
Section: Preparation Of Triphentl Tin(iv) Complexmentioning
confidence: 99%
“…Metal complexes gain tremendous consideration in medicinal chemistry because of their marked and enormous biological properties (1) . They are used as anticancer (2) , antimicrobial (3,4) , antiviral (5) , antiparasitic (6) , antimalarial (7) , antifungi (8) agents. Significance of "coordination chemistry is escalating constantly with the synthesis of organic ligand/s containing" assorted donor groups (9) .…”
Section: Introductionmentioning
confidence: 99%